Therapeutic mammoplasty allows for clear surgical margins in large and multifocal tumours without delaying adjuvant therapy. Issue 2 (April 2015) - Bamford, Richard; Sutton, Richard; McIntosh, Jamie
Abstract Introduction Therapeutic mammoplasty (TM) is suggested to have a number of advantages by comparison to standard breast conservation surgery in selected patients, however, data to support such assertions are sparse and outcomes remain uncertain. We assess the ability of TM to achieve some of its suggested benefits, specifically obtaining clear surgical margins (CSM) around large or multifocal tumours, and examine whether TM is associated with delay in administering adjuvant therapies. Method Data were extracted from a prospectively maintained database on all patients undergoing TM over 8 years. Key oncological outcomes and time to initiation of adjuvant therapies were recorded. Results Sixty eight patients underwent TM, sixty two for invasive disease and six for in-situ disease only. Tumour size ranged from 3 mm to 85 mm. Twenty-one (30.8%) patients received neo-adjuvant therapy, with 15 (22.0%) receiving chemotherapy and six (8.8%) receiving endocrine therapy prior to surgery. CSM were obtained in 65 patients (95.6%). Where margins were involved, two were due to Ductal Carcinoma in situ and one from undiagnosed invasive lobular cancer, resulting in one wider excision and two completion mastectomies. Radiotherapy was delayed in one patient with delayed wound healing. No local recurrence has been recorded. Conclusion These data support the ability of TM to consistently achieve CSM around large and multifocal tumours in selected patients, with acceptable local control and minimal morbidity and delay in adjuvant therapies.